Self-Sufficiency as a Factor in the Development of the System of Psychological Self-Regulation of Personality. - Собкова, Світлана; Бігун, Нелля; Алєксєєва, Юлія; Єльчанінова, Тетяна; Мешко, Олександр (My University, 2023)
n the conditions of transformation of contemporary society there are dynamic transformations, which primarily affect changes in the individual psychological sphere of each person. These changes lead to formation of a holistic, confident and self-sufficient personality, capable of high self-regulation and self-control, which will ensure one’s successful integration into society. The purposeof the article is to substantiate the importance of self-sufficiency in the development of the system of personality self-regulation. The article uses a theoretical analysis of scientific publications on self-regulation and self-sufficiency of the individual; generalization and systematization of the results of current researches and approaches. The considered main approaches to the study of self-regulation, which reflects a conscious control of behavior, contributes to the effective achievement of goals, ensures successful adaptation to changing environmental conditions. Self-regulation includes a whole system of emotional and behavioral reactions, personality traits, internal and external factors that determine one’s development, among which an important place is occupied by self-sufficiency. Self-sufficient personality has a well-established system of claims, autonomy and independence, high self-esteem and determination. Self-sufficiency is associated with personality-oriented growth, self-realization, which provides motivation to effectively regulate behavior and psycho-emotional state. The conducted theoretical research allowed to state that self-regulation of personality is a complex and multidimensional phenomenon, an important place in the structure of which is occupied by self-sufficiency. It is concluded that there isa necessity to update and achieve self-sufficiency, which will promote development of self-regulation
Revista Romaneasca Pentru Educatie Multidimensionala
Keywords: elf-control, adaptation, self-efficacy, perseverance, motivation for achievement, purposefulness.